ANALISIS KANDUNGAN METABOLIK SEKUNDER PADA DAUN KENIKIR (Cosmos Caudatus Kunth.) DENGAN PELARUT METANOL, ETANOL, DAN ETIL ASETAT - Masitah, Masitah; Pribadi, Teguh; Pratama, Mohammad Indra; Harrist, Reynaldi Ferdhani; Sari, Prita Asminitya; Dianita, Feby; Setiawan, Volta Kellik (BIOEDUKASI (Jurnal Pendidikan Biologi), 2023)
Cosmos Caudatus Kunth. is one of the most commonly found medicinal plants.   Cosmos leaves contain phytochemical compounds such as terpenoids, fatty acids, flavonoids, alkaloids, tannins, and saponins. This study aims to determine the effect of differences in methanol, ethanol, and ethyl acetate solvents on the phytochemical tests of  Cosmos leaf samples. The study was conducted in the Biology Education Laboratory, Faculty of Teacher Training and Education, Mulawarman University, as well as the Organic Chemistry Laboratory, Faculty of Mathematics and Natural Sciences, Mulawarman University. Qualitative phytochemical screening is conducted by assessing the solubility qualities of the substances. The findings from the examination of secondary metabolic chemicals indicate that the methanol extract derived from Cosmos leaves comprises alkaloids, triterpenoids, flavonoids, phenolics, and quinones. While the ethanol extract of Cosmos leaves contains alkaloids, flavonoids, saponins, phenolics, and quinones. There is an ethyl acetate extract of Cosmos leaves, alkaloids, steroids, flavonoids, phenolics, and quinones.